Protocol of Life Cycle Cost (LCC) data input requirements process - Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (2016)
Life Cycle Cost (LCC) is an important economic assessment technique that is applied in the beginning of the project to provide useful cost information to the Government, clients, cost estimators and researchers in facilitating them to make better decision in the process of determining the most optimum total ownership costs of an asset or in comparing the most cost-effective of mutually exclusive alternatives. The LCC analysis process can be categorized into three main phases, i.e. data input, conversion and output. The literature study has established that the lack of reliable and current cost data inputs, including sufficient theory has caused difficulties for the estimators to practice LCC analysis. In addition, there is no model, system or guideline has been established in the Malaysian construction industry that can facilitate the LCC estimators to trace, define, collect and update cost data as inputs into the process of producing reliable LCC outputs.